Involving Disabled People in HIV and AIDS Risk Reduction Programmes in Binga District, Zimbabwe - Munsaka, Edson (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2011)
The term "disaster" now forms part of our everyday vocabulary. Current attention focused on floods, famines, tsunamis and earthquakes has, arguably, undermined attention on the devastating effects of another "disaster", the HIV/AIDS pandemic. Increased attention to disaster occurrences across the globe has injected greater interest in understanding the nature of risks posed and vulnerabilities experienced in the face of a range of "disasters". An emphasis on risk reduction occupies the core of the disaster management paradigm that values the participation of those "at risk".This article presents the findings of a small scale empirical study designed to explore the involvement of disabled people in HIV/AIDS risk reduction programmes in Binga District, Zimbabwe. It exposes the systematic exclusion of disabled people from such programmes, and argues that deaf people, those with learning difficulties and disabled women appear to be particularly vulnerable to exclusion from such programmes.